The Effectiveness of the Polya Model Problem Solving Method on Student Learning Outcomes in Solving Math Story Problems - A. Muhajir Nasir; Syartina Syartina (EduMa: Mathematics education learning and teaching, 2021)
This study aims to determine and measure the effectiveness of the application of the Polya model problem-solving method. This research method uses experimental research with the type of research that is quantitative research with one group pretest-posttest design. The results of data analysis showed that the average pre-test of 44.66 based on the criteria of learning outcomes was in a low category while the average post-test was 83.22 which was in the high category. The average normalized gain score is 0.71 in the high category and is normally distributed for learning outcome data. Based on the t-test obtained 0,000 < Â½Î± = 0.025, which means there is a significant increase. The post-test also showed that out of 32 students there were 30 participants (93.75%) who had achieved the KKM scores in mathematics in 11 Maros Baru Junior High School. The results of this study indicate that there is a significant increase in mathematics learning outcomes of students after being taught with the Polya Model Problem Solving method on rectangular material or it can be said that the Polya Model Problem Solving method is effectively applied to the rectangular flat figure material of mathematical story problems.